Inter-individual differences in regulatory strategies in infancy: a pilot study utilizing eye-tracking technology - Schwant, Erin (Kansas State University, 2017)
The mother-infant relationship affects the child’s exploratory and separation behavior, how the child perceives strangers, and significantly impacts the conceptual framework of typical social relationships in the infant’s brain. The purpose of this study was to examine infants’ regulatory strategies, specifically, the relationship between the mother-infant dyad, and the infant’s response to a stressful situation. Eight, 5-month-old infants and their mothers participated in the Face-to-Face Still-Face experiment and a play session to assess maternal sensitivity. Data from the mother-infant dyads were collected during each phase of the Face-to-Face Still-Face paradigm (i.e., play, still-face, and reunion). Maternal sensitivity was assessed using an adapted version of Ainsworth’s four scales of maternal sensitivity. The infant’s strategies for re-engagement with the mother were assessed using eye-tracking methodology to identify specific eye gaze behaviors used during each phase of the still-face experiment. The infants who had more sensitive mothers showed an increase in fixation duration during the reunion phase of the procedure, which could be indicative of a trusting relationship in which the child knows the mother is there to help them regain control of their emotions. Implications of these findings are discussed for the use of eye-tracking methodology as a more flexible and potentially more accurate measure of studying infants’ patterns of ocular focus.
Keywords: Infancy; Eye-tracking; Attachment